Sarcopenia impairs survival in patients with potentially curable hepatocellular carcinoma. Issue 2 (12th August 2015) - Levolger, Stef; van Vledder, Mark G.; Muslem, Rahat; Koek, Marcel; Niessen, Wiro J.; de Man, Rob A.; de Bruin, Ron W. F.; Ijzermans, Jan N. M.
<x xml:space="preserve">Abstract</x> Background A reduction in skeletal muscle mass (sarcopenia) independently predicts poor survival in patients with hepatocellular carcinoma (HCC) undergoing treatment with curative intent. Whether this is due to an increased risk of recurrence and disease specific death, or due to an increased risk of postoperative morbidity and mortality is currently unclear. In this study, we investigate the association between sarcopenia and death in a cohort of HCC patients undergoing treatment with curative intent. Methods Patients undergoing surgical resection or radiofrequency ablation for lesions ≤ 3 cm between 2002 and 2013 were identified. Clinicopathological characteristics, CT‐assessed sarcopenia and outcomes were analyzed. Results Among 90 patients, 52 (57.8%) were found to be sarcopenic. Sarcopenic patients had a limited overall survival (median: 33 months vs. non‐sarcopenic median: 105 months; P = 0.002), but not disease‐free survival. Sarcopenia was an independent predictor for overall survival in multivariate Cox‐regression analysis (HR 3.756; P = 0.001). Major complications (32.7% vs. 13.2%, P = 0.033) and treatment‐related mortality (17.3% vs. 2.6%, P = 0.029) were more frequent in sarcopenic patients. Conclusion Sarcopenia impairs survival in patients with potentially curable hepatocellular carcinoma, mainly due to an increase in treatment‐related mortality. J. Surg. Oncol. 2015 111:208–213. © 2015 Wiley Periodicals, Inc.